2000
DOI: 10.1111/j.1095-8649.2000.tb02225.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gene flow estimates between species of darters in different streams

Abstract: Allozyme variation was assessed at two localities for 38 loci in Etheostoma blennioides and 43 loci in E. flabellare. Percent polymorphism (P) ranged from 18·4 to 31·6 and average heterozygosity (H) ranged from 0·026 to 0·079. Estimates of gene flow indicated panmictic populations of E. blennioides and sub-divided populations of E. flabellare, with significantly more substructuring of E. flabellare from one population. Population structuring of E. flabellare and no structuring of E. blennioides is consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Tributary-related levels of variation are reported for Etheostoma flabellare (Faber & White, 2000), and in Salmo trutta, microsatellite variation seems related to waterfalls and tributaries (Carlsson et al, 1999). In continental species of fish, isoenzyme variation in tributaries is apparently responsible for 22.2% (Ward et al, 1994) to 32.8% (Gyllensten, 1985) of total genetic variation.…”
Section: Discussionmentioning
confidence: 90%
“…Tributary-related levels of variation are reported for Etheostoma flabellare (Faber & White, 2000), and in Salmo trutta, microsatellite variation seems related to waterfalls and tributaries (Carlsson et al, 1999). In continental species of fish, isoenzyme variation in tributaries is apparently responsible for 22.2% (Ward et al, 1994) to 32.8% (Gyllensten, 1985) of total genetic variation.…”
Section: Discussionmentioning
confidence: 90%
“…Greater genetic divergence of the Blanchard River sample in western Lake Erie from tributaries in the central basin (Chagrin, Cuyahoga and Grand Rivers) reflects their general geographic distances. The Blanchard River sample shares some mtDNA haplotypes with the other Lake Erie tributaries, but because the E. caeruleum has limited dispersal capabilities (Paine, 1984; Faber & White, 2001), this probably represents a common glacial refugium ancestry. The star pattern observed in the haplotype networks and mismatch distribution analyses suggests that haplotypes underwent rapid genetic radiation during the glacial–interglacial cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies based on allozyme electrophoresis and mtDNA sequences on populations of Greenside Darter in the United States showed that gene flow varies among regions studied (Heithaus and Laushman 1997;Turner and Trexler 1998). Faber and White (2000) found no significant divergence between populations in two unconnected Ohio River tributaries, whereas Turner (2001) found populations within a 66-km study area in the Spring River, Arkansas were significantly divergent.…”
Section: Introductionmentioning
confidence: 87%